The Ecosystem of Cryptocurrency as an Object of Civil Rights in BRICS Countries - N. Dulatova; Abd Hakim Abd Razak (BRICS Law Journal)
The article presents a comparative legal analysis of the modern legal regulation of the multidimensionality of digital electronic currency in BRICS countries. It assesses the possibility of civil circulation of a digital property right as an economic and legal segment without clear legal regulation. It analyzes the judicial practice related to confidentiality, acquisition, and trading of virtual currency. The article justifies the ability to integrate a single digital currency – CRYPTOBRICS, a single equivalent for all payments in the form of cryptocurrency within the framework of BRICS for settlements and increase in the trade exchange volume on these international platforms. This will provide for the legalization and consolidation of the legal framework of cryptocurrency within the context of objects of civil rights, allowing BRICS members to become regulatory leaders in the field of digital assets. We formulated a proposal to create an international agreement defining the parameters of the digital currency issue based on blockchain technology for interstate transactions, which allows the BRICS counties to establish the next stage of their mutual integration for the free trade zone and the customs union. Unifying the civil circulation of cryptocurrency and using the platform of modern non-monetary digital circulation as our foundation, we concluded that BTC can be classified as a type of digital property right. The article justified the theoretical definition of digital property right in the form of cryptocurrency as a resource stored in a device or electronic system which allows the end user to complete transactions using virtual currency and denominated in another payment unit, as opposed to currencies issued by sovereign states. We suggested that insurance companies be insured against all possible risks associated with cryptocurrency circulation and cybersecurity as a civil measure to protect the order of intangible digital codes – cryptocurrencies.